Graphite-based metal catalyst precursor, preparation method thereof, graphite-based metal catalyst and application of graphite-based metal catalyst precursor and graphite-based metal catalyst
By growing metal organic frame materials of Co and Fe in situ on the graphite surface, combined with high-temperature annealing and chemical vapor deposition technology, the problem of difficulty in removing impurities and catalyst agglomeration in the expanded vermiculite support is solved, and efficient preparation of ordered array carbon nanometers is achieved Improve productivity and quality.
Patent Information
- Application Number
- CN202411308455.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-24
AI Technical Summary
In the prior art, when expanding vermiculite is used as a support to prepare array carbon nanotubes, it is difficult to completely remove impurities, which increases the difficulty and cost of purification of carbon nanotubes. In addition, metal catalysts are prone to agglomeration during high-temperature catalysis, affecting yield and quality.
Using graphite as a support, metal organic frame materials including Co and Fe are grown in situ on its surface by hydrothermal method to form graphite/metal organic frame composites for catalyzing the growth of array carbon nanotubes, combining high-temperature annealing and chemical gas phase Deposition technology.
The uniform dispersion of active metal sites is achieved, the catalytic activity and yield and quality of carbon nanotubes are improved, and the difficulty of removing impurities and production costs are reduced. The carbon nanotubes are arranged in a relatively orderly manner, which improves electron conduction and processability.
Smart Images

Figure CN119175110A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of nanomaterials, and specifically, relates to a graphite-based metal catalyst precursor and a preparation method thereof, a graphite-based metal catalyst, and the application of the graphite-based metal catalyst precursor and the graphite-based metal catalyst in the preparation of array carbon nanotubes. Background Art
[0002] Carbon nanotubes (CNTs) have excellent properties such as high electrical and thermal conductivity, high mechanical strength, high aspect ratio, high specific surface area and chemical resistance, and have broad application prospects in engineering materials, electronic devices, energy, environmental engineering, biomedicine and other fields. Carbon nanotubes that usually grow on disordered catalysts have a clustered structure and are severely entangled, making subsequent dispersion and other processing and application processes difficult. However, array-type carbon nanotubes are generally better in conductivity and processability than entangled carbon nanotubes due to their orderly arrangement and good orientation.
[0003] At present, expanded vermiculite (layered silicate mineral) is usually used as a carrier of metal catalysts to prepare array-type carbon nanotubes in industrial production. Its rich layered structure and good interlayer cation exchange capacity enable the active metal catalyst to be smoothly intercalated and anchored, providing sufficient space and active sites for the growth of carbon nanotube arrays. However, the presence of silicates in the vermiculite skeleton causes the prepared array-type carbon nanotube products to contain impurities such as ash and silicon oxide, which are difficult to completely remove through ordinary acid washing processes, which increases the difficulty of purification and use cost of carbon nanotubes.
[0004] Therefore, it is necessary to develop new methods for preparing arrayed carbon nanotubes. Summary of the invention
[0005] In view of the above problems existing in the prior art, the purpose of the present application is to provide a graphite-based metal catalyst precursor and a preparation method thereof, a graphite-based metal catalyst, and the use of the graphite-based metal catalyst precursor and the graphite-based metal catalyst in the preparation of array-type carbon nanotubes. The graphite-based metal catalyst precursor and the catalyst can replace expanded vermiculite to prepare array-type carbon nanotubes, and have high catalytic activity and target product yield.
[0006] The first aspect of the present application provides a method for preparing a graphite-based metal catalyst precursor, comprising:
[0007] (1) Providing reaction solution A and reaction solution B
[0008] The graphite oxide, the soluble metal salt and water are first mixed to obtain the reaction solution A; wherein the soluble metal salt includes a cobalt salt and an iron salt;
[0009] The organic ligand, the alkali solution and the water are mixed for the second time to obtain the reaction solution B;
[0010] (2) The reaction solution A and the reaction solution B are mixed for a third time to form a metal organic framework material including cobalt (Co) and iron (Fe) on the surface of the graphite oxide.
[0011] The preparation method provided by the present application is to grow a metal organic framework material including Co and Fe in situ on the surface of graphite oxide by a hydrothermal method, and the graphite-based metal catalyst precursor belongs to a graphite / metal organic framework material composite. Wherein, graphite oxide is rich in hydrophilic oxygen-active functional groups, and a metal organic framework material with uniformly dispersed active metal sites can be uniformly loaded on the surface of graphite interlayers by a simple hydrothermal method, so that in the subsequent process of forming carbon nanotubes, the catalyst active components can give full play to their activity and are not easy to agglomerate, which is conducive to the in-situ catalytic formation of array-type carbon nanotubes on the surface of graphite interlayers. In addition, Fe and Co are simultaneously included in the active component, and the two metals are used in combination, which can effectively improve the catalytic activity while promoting the formation of organic framework materials, so that the yield and quality of the carbon nanotubes prepared subsequently can be improved.
[0012] In some embodiments of the present application, the preparation method further comprises: immersing the graphite in concentrated nitric acid, adding potassium permanganate and acetic acid, and performing an oxidation reaction to prepare the graphite oxide. Using concentrated nitric acid and potassium permanganate as oxidants and acetic acid as a layer intercalant can improve the surface activity of the graphite, promote the combination of the graphite and the active components of the catalyst, and the uniform distribution of the active components.
[0013] Furthermore, relative to 1 g of the graphite, the amount of the concentrated nitric acid is 5-10 mL, and the amount of the acetic acid is 2-5 mL; the mass ratio of the graphite to potassium permanganate is (1.5-3):1.
[0014] Furthermore, the temperature of the oxidation reaction is 20-40° C., and the time is 0.5-2 h.
[0015] In some embodiments of the present application, the molar ratio of the iron salt to the cobalt salt is (1.2-7):1.
[0016] In some embodiments of the present application, the cobalt salt is selected from at least one of cobalt chloride, cobalt nitrate, cobalt sulfate and their respective hydrates.
[0017] In some embodiments of the present application, the iron salt is selected from at least one of ferric chloride, ferric nitrate, ferric sulfate and their respective hydrates.
[0018] In some embodiments of the present application, the mass ratio of the graphite oxide to the soluble metal salt is (15-30): 100. Thus, the possibility of relatively low active metal loading and low carbon nanotube yield due to excessive graphite oxide carriers can be reduced, and the stacking and agglomeration that is easy to occur during the growth of the metal organic framework due to too little graphite oxide carriers can be avoided as much as possible, which affects the utilization rate of the active components.
[0019] In some embodiments of the present application, the organic ligand is at least one of 2-methylimidazole, terephthalic acid and phthalic acid.
[0020] Furthermore, the organic ligand is 2-methylimidazole.
[0021] In some embodiments of the present application, the mass ratio of the organic ligand to the soluble metal salt is (20-50):100.
[0022] In some embodiments of the present application, the alkali solution is selected from at least one of triethylamine, ammonia water and an aqueous solution of sodium hydroxide.
[0023] In some embodiments of the present application, the amount of the alkali solution used is 0.2 to 0.8 mL relative to 1 g of the organic ligand.
[0024] Furthermore, relative to 1 g of the organic ligand, the amount of the alkali solution used is 0.3 to 0.5 mL.
[0025] In some embodiments of the present application, in step (2), the third mixing is performed under stirring conditions, the stirring speed is 500-1200 rpm, and the temperature of the third mixing is 50-80° C., and the time is 0.5-3 hours. High-speed stirring and high-temperature reaction can reduce the grain size of the synthesized metal organic framework material and provide more active sites.
[0026] The second aspect of the present application provides a graphite-based metal catalyst precursor prepared by the preparation method described in the first aspect of the present application.
[0027] In the graphite-based metal catalyst precursor of the present application, the metal-organic framework material can provide uniformly dispersed active metal sites, has excellent anti-agglomeration performance in the subsequent high-temperature catalytic process, and can improve the utilization rate of the catalytic metal and the conversion rate of the carbon source.
[0028] The third aspect of the present application provides a graphite-based metal catalyst, which is prepared by annealing the graphite-based metal catalyst precursor described in the second aspect of the present application under an inert atmosphere.
[0029] The graphite-based metal catalyst precursor of the present application is subjected to high-temperature annealing treatment under an inert atmosphere, and the metal-organic framework material therein can be converted into metal nanoparticles and a carbon skeleton, and the metal nanoparticles are fixed on the carbon skeleton to provide space and active sites for the growth of carbon nanotubes. Therefore, the provided graphite-based metal catalyst is conducive to the growth of array-type carbon nanotubes.
[0030] In some embodiments of the present application, the annealing temperature is 650-750° C., and the time is 20-70 minutes.
[0031] The fourth aspect of the present application provides the use of the graphite-based metal catalyst precursor described in the second aspect of the present application or the graphite-based metal catalyst described in the third aspect of the present application in the preparation of array-type carbon nanotubes.
[0032] The fifth aspect of the present application provides a method for preparing an array-type carbon nanotube / graphite hybrid material, comprising: under inert gas protection, in the presence of a catalytic material, using a carbon source gas to perform chemical vapor deposition to form an array of carbon nanotubes, thereby preparing the array-type carbon nanotube / graphite hybrid material; wherein the catalytic material comprises the graphite-based metal catalyst precursor described in the second aspect of the present application or the graphite-based metal catalyst described in the third aspect of the present application.
[0033] In some embodiments of the present application, the carbon source gas is selected from at least one of methane, ethane, propane, acetylene, ethylene and propylene. In this case, the carbon source gas can be decomposed during the chemical deposition process and provide hydrogen to maintain catalytic activity.
[0034] In some embodiments of the present application, the chemical vapor deposition conditions include: a carbon source gas flow rate of 1000 to 3000 sccm, a temperature of 650 to 750° C., and a time of 40 to 70 minutes.
[0035] In some embodiments of the present application, the amount of the catalytic material is 0.1-2 g relative to 1000 sccm of the carbon source gas.
[0036] In the preparation method of the present application, the carbon nanotubes are restricted by the graphite layered structure during the growth process, forming a relatively orderly array of carbon nanotubes, thereby constituting an array of carbon nanotube / graphite hybrid material. Compared with the simple mechanical compounding of the two materials, the hybrid material has better electronic conduction and processability.
[0037] To this end, the sixth aspect of the present application provides an array-type carbon nanotube / graphite hybrid material prepared by the preparation method described in the fifth aspect of the present application.
[0038] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0040] Figure 1 A sample photo of the array-type carbon nanotube / graphite hybrid material prepared in Application Example 2;
[0041] Figure 2 This is a scanning electron microscope (SEM) image of the array-type carbon nanotube / graphite hybrid material prepared in Application Example 2. DETAILED DESCRIPTION
[0042] The following describes the implementation of the present application in detail. The implementation described below is exemplary and is only used to explain the present application, and cannot be understood as limiting the present application.
[0043] The "range" disclosed in the present application is defined in the form of a lower limit and / or an upper limit, and a given range is defined by selecting a lower limit and / or an upper limit. The range defined in this way can be inclusive or exclusive of end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form an unclearly recorded range, and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, each separately disclosed point or single value itself can be combined with any other point or single value as a lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0044] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0045] Graphite is an allotrope of carbon with a three-dimensional structure formed by stacking multiple layers of planes. After physical and chemical treatment, it can show a rich layered structure and a large specific surface area, which will be conducive to the controllable loading of metal catalysts. Using graphite instead of vermiculite as a catalyst carrier is expected to improve the subsequent purification efficiency of array-type carbon nanotubes (some impurities contained in vermiculite are difficult to completely remove by ordinary acid washing, or, in order to improve the impurity removal rate, a longer reaction time or a stronger acid is required, such as HF). However, due to the strong hydrophobicity of graphite itself, it is difficult for metal catalysts to be transferred and fixed between graphite layers through aqueous solutions. They are more deposited on the outer edge of the graphite layer, which leads to low catalytic activity of graphite-based metal catalysts, and metal particles are very easy to agglomerate during high-temperature catalysis, and the utilization rate of metal active sites is low, which affects the yield and quality of carbon nanotubes. Although the use of certain organic solvents (such as alcohols) can improve this deficiency, the ability of organic solvents to dissolve metal salts is limited, and there is a certain toxicity or danger, which is not conducive to industrial production.
[0046] To this end, in a first aspect, the present application provides a method for preparing a graphite-based metal catalyst precursor, wherein the graphite-based metal catalyst precursor is a graphite / metal organic framework material composite, and the preparation method comprises the following steps:
[0047] (1) Provide reaction solution A and reaction solution B separately
[0048] The graphite oxide, the soluble metal salt and water are first mixed to obtain the reaction solution A; the organic ligand, the alkali solution and water are second mixed to obtain the reaction solution B;
[0049] (2) The reaction solution A and the reaction solution B are mixed for a third time to form a metal organic framework material including Co and Fe on the surface of the graphite oxide.
[0050] In the preparation method of the present application, a metal organic framework material including Co and Fe is grown in situ on the surface of graphite oxide. Graphite oxide is rich in hydrophilic oxygen-active functional groups, and water can be used as a solvent. Through a mild hydrothermal method, a metal organic framework material with uniformly dispersed active sites can be loaded on the surface of the graphite interlayer. In addition, the simultaneous introduction of Fe and Co into the metal active components can not only promote the formation of an organic framework structure, but also improve the catalytic activity. In this way, the prepared graphite-based metal catalyst precursor is used as a catalytic material to improve the yield and quality of carbon nanotubes.
[0051] In the present application, the graphite oxide can be prepared by oxidizing graphite. According to some embodiments, the preparation method further comprises the following step of preparing the graphite oxide: immersing the graphite in concentrated nitric acid, adding potassium permanganate and acetic acid, and performing an oxidation reaction.
[0052] As some examples, the mass concentration of the concentrated nitric acid may be 68% to 98%.
[0053] In some embodiments, relative to 1 g of the graphite, the amount of concentrated nitric acid used is 5 to 10 mL, for example, 5 mL, 6 mL, 7 mL, 8 mL, 10 mL, etc., and the amount of acetic acid used is 2 to 5 mL, for example, 2 mL, 2.5 mL, 3 mL, 4 mL, 5 mL, etc.
[0054] In some embodiments, the mass ratio of the graphite to potassium permanganate is (1.5-3):1, for example, 1.5:1, 1.8:1, 1.9:1, 2:1, 2.2:1, 3:1, etc.
[0055] In some embodiments, the oxidation reaction temperature is 20-40°C, for example, 20°C, 25°C, 30°C, 35°C, 40°C, etc., and the oxidation reaction time is 0.5-2h, for example, 0.5h, 1h, 1.5h, 2h, etc.
[0056] As some examples, in order to obtain high-purity graphite oxide, the step of preparing graphite oxide further includes: filtering, washing, and drying the product obtained from the oxidation reaction. The drying temperature can be 60 to 90° C., such as 60° C., 70° C., 80° C., 90° C., etc., and the drying time can be 4 to 12 hours, such as 4 hours, 5 hours, 8 hours, 10 hours, 12 hours, etc.
[0057] In step (1), the soluble metal salt refers to a metal salt that can be dissolved in water. The soluble metal salt includes cobalt salts and iron salts. The present application does not particularly limit the cobalt salts and iron salts, as long as they can be dissolved in water and provide cobalt ions and iron ions to the reaction solution A.
[0058] In some embodiments, the cobalt salt is selected from at least one of cobalt chloride, cobalt nitrate, cobalt sulfate and their respective hydrates. Further, the cobalt salt is cobalt chloride hydrate (such as CoCl 2 6H 2 O), cobalt nitrate hydrate (such as Co(NO 3 ) 2 6H 2 O) and cobalt sulfate hydrate (such as CoSO 4 7H 2 O) in one or more.
[0059] In some embodiments, the iron salt is selected from at least one of ferric chloride, ferric nitrate, ferric sulfate and their respective hydrates. Further, the iron salt is ferric chloride hydrate (such as FeCl 3 6H 2 O), ferric nitrate hydrate (such as Fe(NO 3 )3 9H 2 O) and iron sulfate hydrate (such as Fe 2 (SO 4 ) 3 6H 2 O) in one or more.
[0060] In step (1), the mass ratio of the iron salt to the cobalt salt can be (1-15):1, for example, 1:1, 2:1, 2.5:1, 3:1, 4:1, 4.5:1, 5:1, 6:1, 8:1, 12:1, 15:1, etc.
[0061] In some embodiments, the molar ratio of the iron salt to the cobalt salt is (1.2-7):1, such as 1.2:1, 1.6:1, 1.8:1, 2:1, 3:1, 3.2:1, 5:1, 5.8:1, 7:1, etc. Controlling the relative amounts of the two metal salts within this range can not only promote the formation of array-type carbon nanotubes, but also improve the catalytic efficiency.
[0062] In the present application, the amount of the graphite oxide can be determined according to the amount of the soluble metal salt. Too much graphite oxide carrier may lead to a relatively low loading of active metals, affecting the yield of carbon nanotubes; too little graphite oxide carrier may lead to an excessively high loading of active metals, and the metal organic framework material may be prone to agglomeration during the growth process, affecting the utilization rate of the active components. According to some embodiments, the mass ratio of the graphite oxide to the soluble metal salt is (15-30):100, for example, 15:100, 20:100, 25:100, 27:100, 30:100, etc.
[0063] The present application does not particularly limit the conditions for the first mixing, as long as the soluble metal salt can be dissolved and the graphite oxide can be evenly dispersed. According to some embodiments, the first mixing is performed under stirring conditions, the temperature can be 40 to 60° C., and the stirring time can be 30 to 60 minutes.
[0064] In step (1), the amount of water in the reaction solution A can be determined according to the mass of the graphite oxide. According to some embodiments, the amount of water can be such that the mass concentration of graphite oxide in the obtained reaction solution A is 20 to 60 mg / mL.
[0065] In the present application, the organic ligand can be selected from various organic ligands containing nitrogen atoms and oxygen atoms. According to some embodiments, the organic ligand is at least one of 2-methylimidazole, terephthalic acid and phthalic acid.
[0066] Preferably, the organic ligand is 2-methylimidazole. 2-methylimidazole is combined with metal ions to form a metal organic framework that can effectively fix and separate metals, and the metal organic framework has high porosity and specific surface area, and can effectively adsorb metal ions that are not involved in the coordination in the solution, thereby increasing the active metal loading of the catalyst.
[0067] In the present application, the amount of the organic ligand can be determined according to the mass of the soluble metal salt. According to some embodiments, the mass ratio of the organic ligand to the soluble metal salt is (20-50):100, for example, 20:100, 25:100, 30:100, 35:100, 36:100, 40:100, 44:100, 50:100, etc.
[0068] In the present application, the alkali solution can generally promote the formation of the metal organic framework and achieve the regulation of the morphology. According to some embodiments, the alkali solution is selected from at least one of triethylamine, ammonia water and an aqueous solution of sodium hydroxide. Generally, the molar concentration of NaOH in the aqueous solution of sodium hydroxide is 1 to 5 mol / L.
[0069] Preferably, the alkali solution is aqueous ammonia.
[0070] In some embodiments, the amount of the alkali solution is 0.2-0.8 mL, such as 0.2 mL, 0.3 mL, 0.4 mL, 0.5 mL, 0.6 mL, 0.8 mL, etc., relative to 1 g of the organic ligand. Too little alkali solution may lead to incomplete reaction and low metal ion utilization; too much alkali solution is not conducive to the coordination of metal ions and organic small molecules, making it difficult to form a complete framework material, causing metal ions to precipitate prematurely, and making the active components unevenly distributed.
[0071] Preferably, the amount of the alkali solution used is 0.3-0.5 mL relative to 1 g of the organic ligand.
[0072] The present application has no particular limitation on the second mixing method, as long as the organic ligand and the alkaline solution can be dissolved in water to form a homogeneous reaction solution B.
[0073] In step (1), the amount of water in the reaction solution B can be determined according to the amount of the organic ligand. According to some embodiments, the amount of water can be such that the mass concentration of the organic ligand in the obtained reaction solution B is 50-200 mg / mL.
[0074] In step (1), by providing reaction solution A and reaction solution B separately, the subsequent reaction can be stably carried out.
[0075] In the present application, the third mixing of step (2) can achieve the impregnation of metal salts and the coordination polymerization reaction of organic ligands and metal ions to form a metal organic framework material including Co and Fe on the interlayer surface of graphite oxide. As some examples, after the reaction solution A is formed by the first mixing, the reaction solution B is directly added to the reaction solution A and then the third mixing is performed.
[0076] In the present application, the third mixing can be carried out under high-speed stirring conditions, and the high-speed stirring speed is usually not less than 500 rpm. High-speed stirring is conducive to reducing the grain size of the metal organic framework material and providing more active metal sites. Preferably, the stirring speed of the third mixing is 500-1200 rpm.
[0077] In some embodiments, the temperature of the third mixing may be 50-80° C., such as 50° C., 60° C., 70° C., 80° C., etc. This temperature is higher than room temperature, which is beneficial to reducing the grain size of the product on the one hand, and can promote the diffusion of reactants into the graphite interlayer reaction on the other hand, thereby improving the synthesis efficiency.
[0078] In addition, the third mixing time can be 0.5 to 3 hours, for example, 0.5 hours, 1 hour, 2 hours, 3 hours, etc.
[0079] In order to obtain a graphite-based metal catalyst precursor solid product, in some embodiments, the preparation method further comprises: subjecting the product obtained in step (2) to solid-liquid separation, washing, and drying to obtain a graphite-based metal catalyst precursor solid product.
[0080] Preferably, the drying temperature is 90-150° C. and the drying time is 3-8 hours.
[0081] In a second aspect, the present application provides a graphite-based metal catalyst precursor prepared by the preparation method described in the first aspect of the present application.
[0082] The graphite-based metal catalyst precursor of the present application includes a graphite oxide carrier and a metal organic framework material uniformly loaded on the interlayer surface of the carrier. The precursor has uniformly dispersed active metal (including Co and Fe) sites, has excellent anti-agglomeration properties, and can improve the utilization rate of the catalytic metal and the conversion rate of the carbon source.
[0083] In a third aspect, the present application provides a graphite-based metal catalyst, which is prepared by annealing the graphite-based metal catalyst precursor described in the second aspect of the present application under an inert atmosphere.
[0084] The graphite-based metal catalyst precursor of the present application is annealed under an inert atmosphere, and the metal organic framework material therein can be converted into metal nanoparticles and a carbon skeleton. The metal nanoparticles are fixed on the carbon skeleton to provide space and active sites for the growth of carbon nanotubes. Therefore, the provided graphite-based metal catalyst is conducive to the growth of array-type carbon nanotubes.
[0085] In some embodiments, the annealing temperature is 650-750° C., and the annealing time is 20-70 minutes.
[0086] In a fourth aspect, the present application provides the use of the graphite-based metal catalyst precursor described in the second aspect of the present application or the graphite-based metal catalyst described in the third aspect of the present application in the preparation of array carbon nanotubes.
[0087] In some embodiments, the application includes: under the protection of an inert gas, first annealing the graphite-based metal catalyst precursor, then introducing a carbon source and hydrogen, and pyrolyzing the carbon source at a high temperature at an annealing temperature to form array-type carbon nanotubes.
[0088] In other embodiments, the application includes: under the protection of an inert gas, contacting the graphite-based metal catalyst with a carbon source and hydrogen, and subjecting the carbon source to high-temperature cracking at an annealing temperature to form array-type carbon nanotubes.
[0089] In a fifth aspect, the present application provides a method for preparing an array-type carbon nanotube / graphite hybrid material, comprising: under inert gas protection, in the presence of a catalytic material, chemical vapor deposition (CVD) is performed using a carbon source gas to form an array-type carbon nanotube, thereby obtaining the array-type carbon nanotube / graphite hybrid material; wherein the catalytic material includes the graphite-based metal catalyst precursor or the graphite-based metal catalyst.
[0090] According to the preparation method of the present application, carbon nanotubes are formed by self-assembly through high temperature catalytic cracking of carbon sources. During the growth of carbon nanotubes, the restriction of the graphite layered structure is conducive to the formation of relatively orderly array-type carbon nanotubes. It can be understood that because the array-type carbon nanotubes are formed in the presence of the catalytic material, the product obtained is an array-type carbon nanotube / graphite hybrid material.
[0091] In some embodiments, the carbon source used is a hydrogen-containing carbon source gas. The hydrogen generated by cracking this type of carbon source under high temperature conditions also protects the catalyst, further avoiding catalyst failure caused by carbon formation.
[0092] Furthermore, the hydrogen-containing carbon source gas is selected from at least one of methane, ethane, propane, acetylene, ethylene and propylene.
[0093] In some embodiments, the chemical vapor deposition conditions include: a carbon source gas flow rate of 1000 to 3000 sccm, a temperature of 650 to 750° C., and a time of 40 to 70 minutes.
[0094] Preferably, the flow rate of the inert gas is 3000-8000 sccm. In this case, the inert gas can act as a carrier gas and can also avoid rapid failure of the catalyst caused by excessively high carbon source concentration.
[0095] In addition, the inert gas may be nitrogen or argon.
[0096] Preferably, the amount of the catalytic material used is 0.1-2 g, such as 0.2 g, 0.25 g, 0.5 g, 1 g, 1.5 g, etc., relative to 1000 sccm of the carbon source gas.
[0097] In some embodiments, the chemical vapor deposition (CVD) may be performed in the presence of hydrogen gas, with a flow rate of hydrogen gas of 100-150 sccm.
[0098] In the present application, annealing and chemical vapor deposition can be directly performed in a tubular furnace to prepare the array-type carbon nanotube / graphite hybrid material. According to some embodiments, the preparation method includes the following process: introducing an inert gas into a tubular furnace containing the graphite-based metal catalyst precursor, and annealing the furnace at a rate of 5 to 10°C / min to 650 to 750°C; continuing to introduce hydrogen and a carbon source to perform chemical vapor deposition to obtain an array-type carbon nanotube / graphite hybrid material.
[0099] In a sixth aspect, the present application provides an array-type carbon nanotube / graphite hybrid material prepared by the preparation method described in the fifth aspect of the present application.
[0100] The array-type carbon nanotube / graphite hybrid material of the present application has a high conductivity, the combination between the carbon nanotubes and the graphite is more complete, the dispersion is more uniform, and the contact resistance between the two is reduced, and the hybrid material also has a high specific surface area. In addition, compared with the array-type carbon nanotubes prepared with expanded vermiculite as a carrier, the array-type carbon nanotube / graphite hybrid material of the present application can remove the metal catalyst component therein by simple acid washing (such as hydrochloric acid, sulfuric acid, nitric acid, etc.), the purification conditions are mild, and the production cost of the array-type carbon nanotubes can be reduced.
[0101] The following describes embodiments of the present application. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application.
[0102] Preparation Example 1
[0103] This preparation example is used to illustrate the preparation method of the treated graphite used in the following examples and comparative examples.
[0104] 15 g of graphite was soaked in 120 mL of concentrated nitric acid (concentration of 68 wt%) for 10 minutes, and then 8 g of potassium permanganate and 60 mL of acetic acid were added while stirring. The resulting mixture was stirred at 30 ° C for 1 hour, filtered and washed, and the resulting solid was dried at 70 ° C for 10 hours to obtain treated graphite, i.e., graphite oxide.
[0105] The following examples are used to illustrate the graphite-based metal catalyst precursor and the preparation method thereof of the present application.
[0106] Example 1
[0107] 5 g of cobalt nitrate hexahydrate and 40 g of ferric nitrate nonahydrate were dissolved in 300 mL of deionized water, and 13 g of the treated graphite was added, and the resulting mixture was stirred at 50° C. for 30 minutes to obtain a reaction solution A;
[0108] Dissolve 20 g of 2-methylimidazole and 7 mL of aqueous ammonia in 200 mL of aqueous solution to obtain reaction solution B;
[0109] The reaction liquid A and the reaction liquid B were mixed, and the mixture was stirred at 800 rpm for 70 minutes at 80°C, and then filtered and washed. The solid product was dried at 120°C for 5 hours to form a graphite-based iron-cobalt bimetallic organic framework catalyst precursor (i.e., a graphite-based metal catalyst precursor), which was recorded as Cat-1.
[0110] Example 2
[0111] 10 g of cobalt nitrate hexahydrate and 45 g of ferric nitrate nonahydrate were dissolved in 300 mL of deionized water, and 15 g of the treated graphite was added, and the resulting mixture was stirred at 50° C. for 30 minutes to obtain a reaction solution A;
[0112] Dissolve 22.5 g of 2-methylimidazole and 10 mL of aqueous ammonia in 200 mL of aqueous solution to obtain reaction solution B;
[0113] The reaction liquid A and the reaction liquid B were mixed, and the mixture was stirred at 800 rpm for 90 minutes at 70°C, and then filtered and washed. The obtained solid product was dried at 120°C for 5 hours to obtain a graphite-based iron-cobalt bimetallic organic framework catalyst precursor, which was recorded as Cat-2.
[0114] Example 3
[0115] 20 g of cobalt nitrate hexahydrate and 50 g of ferric nitrate nonahydrate were dissolved in 300 mL of deionized water, and 17 g of the treated graphite was added, and the resulting mixture was stirred at 50° C. for 30 minutes to obtain a reaction solution A;
[0116] Dissolve 25 g of 2-methylimidazole and 12 mL of aqueous ammonia in 200 mL of aqueous solution to obtain reaction solution B;
[0117] The reaction liquid A and the reaction liquid B were mixed, and the mixture was stirred at 800 rpm for 100 minutes at 65°C. Finally, the mixture was filtered and washed. The solid product was dried at 120°C for 5 hours to obtain a graphite-based iron-cobalt bimetallic organic framework catalyst precursor, which was designated as Cat-3.
[0118] Example 4
[0119] A graphite-based metal catalyst precursor was prepared according to the method of Example 2, except that the amount of ammonia water was adjusted to 5 mL. The obtained graphite-based metal catalyst precursor was recorded as Cat-4.
[0120] Example 5
[0121] A graphite-based metal catalyst precursor was prepared according to the method of Example 2, except that the amount of ammonia water was adjusted to 15 mL. The obtained graphite-based metal catalyst precursor was recorded as Cat-5.
[0122] Example 6
[0123] 7 g of cobalt chloride hexahydrate and 42 g of ferric chloride hexahydrate were dissolved in 300 mL of deionized water, and 12 g of the treated graphite was added, and the resulting mixture was stirred at 40° C. for 30 minutes to obtain a reaction solution A;
[0124] Dissolve 19 g of 2-methylimidazole and 8 mL of aqueous ammonia in 200 mL of aqueous solution to obtain reaction solution B;
[0125] The reaction liquid A and the reaction liquid B were mixed, and the mixture was stirred at 1000 rpm for 120 minutes at 75°C, and then filtered and washed. The obtained solid product was dried at 100°C for 7 hours to obtain a graphite-based iron-cobalt bimetallic organic framework catalyst precursor, which was recorded as Cat-6.
[0126] Example 7
[0127] 14 g of cobalt chloride hexahydrate and 42 g of ferric chloride hexahydrate were dissolved in 300 mL of deionized water, and 12 g of the treated graphite was added, and the resulting mixture was stirred at 40° C. for 30 minutes to obtain a reaction solution A;
[0128] Dissolve 15.5 g of 2-methylimidazole and 6 mL of aqueous ammonia in 200 mL of aqueous solution to obtain reaction solution B;
[0129] The reaction solution A and the reaction solution B were mixed, and the mixture was stirred at 1000 rpm for 100 minutes at 60°C, and then filtered and washed. The obtained solid product was dried at 100°C for 7 hours to obtain a graphite-based iron-cobalt bimetallic organic framework catalyst precursor, which was recorded as Cat-7.
[0130] Comparative Example 1
[0131] A graphite-based metal catalyst precursor was prepared according to the method of Example 1, except that the untreated graphite in Preparation Example 1 was used as a catalyst carrier. The prepared graphite-based metal catalyst precursor was recorded as Cat-D1.
[0132] Comparative Example 2
[0133] A graphite-based metal catalyst precursor was prepared according to the method of Example 1, except that 2-methylimidazole was not added when preparing the reaction solution B. Specifically,
[0134] Dissolve 7 mL of aqueous ammonia in 200 mL of aqueous solution to obtain reaction solution B;
[0135] The reaction liquid A and the reaction liquid B were mixed, and the mixture was stirred at 800 rpm for 70 minutes at 80°C, and then filtered and washed. The obtained solid product was dried at 120°C for 5 hours to obtain a graphite-based iron-cobalt bimetallic catalyst precursor, which was recorded as Cat-D2.
[0136] Comparative Example 3
[0137] A graphite-based metal catalyst precursor was prepared according to the method of Example 1, except that when preparing the reaction solution A, ferric nitrate nonahydrate was not added. Specifically,
[0138] 34 g of cobalt nitrate hexahydrate was dissolved in 300 mL of deionized water, and 13 g of the treated graphite was added, and the resulting mixture was stirred at 50° C. for 30 minutes to obtain a reaction solution A;
[0139] The reaction liquid A and the reaction liquid B were mixed, and the mixture was stirred at 800 rpm for 70 minutes at 80°C, and then filtered and washed. The obtained solid product was dried at 120°C for 5 hours to obtain a graphite-based cobalt metal organic framework catalyst precursor, which was recorded as Cat-D3.
[0140] Application Example 1
[0141] 1g Cat-1 was spread in a quartz boat, placed in a tube furnace, introduced with argon, and the furnace temperature was raised to 700°C at a heating rate of 10°C / min, annealed at this temperature for 30 minutes, and hydrogen and propylene were continuously introduced for chemical vapor deposition, reacted for 60 minutes, cooled to room temperature after the reaction, and the product (array-type carbon nanotube / graphite hybrid material) was collected. Among them, the argon flow rate was 5000sccm, the hydrogen flow rate was 120sccm, and the propylene flow rate was 2500sccm.
[0142] Application Examples 2 to 7
[0143] An array-type carbon nanotube / graphite hybrid material was prepared according to the method of Application Example 1, except that the catalyst precursor Cat-1 was replaced by Cat-2 to Cat-7 respectively.
[0144] Application Comparative Examples 1 to 3
[0145] An array-type carbon nanotube / graphite hybrid material was prepared according to the method of Application Example 1, except that the catalyst precursor Cat-1 was replaced by Cat-D1 to Cat-D3 respectively.
[0146] The performance of the array-type carbon nanotube / graphite hybrid material was tested using the following method.
[0147] 1. Growth rate: The calculation formula is, growth rate = output / active catalyst dosage; wherein, output refers to the mass of graphite / carbon nanotube hybrid material, in g; active catalyst dosage refers to the amount of graphite-based metal catalyst precursor, in g.
[0148] 2. Resistivity: Use GM-I multifunctional powder resistivity automatic tester to test the powder resistivity.
[0149] 3. Specific surface area: The specific surface area is tested using a dynamic nitrogen adsorption-desorption specific surface area meter.
[0150] The test results are shown in Table 1.
[0151] Table 1
[0152]
[0153]
[0154] Combined with the results in Table 1, by comparing Application Examples 1 to 7 with Application Comparative Examples 1 to 3, it can be seen that when the precursors of Examples 1 to 7 are used to catalyze the preparation of carbon nanotubes, the carbon nanotubes have a higher growth rate, and the products have higher conductivity and specific surface area. In Comparative Example 1, treated graphite is not used, resulting in low catalyst loading, uneven loading, and inability to effectively synthesize array-type carbon nanotubes.
[0155] Comparing Application Example 1 with Application Comparative Example 1, it can be seen that, compared with untreated graphite (Comparative Example 1), using the treated graphite (graphite oxide) as a catalyst carrier can increase the loading amount of the active metal catalyst, thereby increasing the growth rate and reducing the resistivity of the product.
[0156] By comparing Application Example 1 with Application Comparative Example 2, it can be seen that the precursor of Example 1 has a higher growth rate when used to catalyze the preparation of carbon nanotubes. It can be seen that after the metal organic framework material is annealed, uniformly dispersed active metal sites are obtained, which can effectively alleviate the aggregation phenomenon during high-temperature catalysis, thereby improving the utilization rate of active metals. In Comparative Example 2, no organic ligand is added, and the catalyst precursor is prepared by precipitation method, which easily leads to agglomeration of active components, inability to load evenly, and greatly reduces the adhesion ability on the graphite surface, making it impossible for the active components to diffuse between layers, resulting in low catalytic activity and inability to synthesize array-type carbon nanotubes.
[0157] Comparing Application Example 1 with Application Comparative Example 3, it can be seen that using cobalt metal alone as the active component (Comparative Example 3) cannot effectively synthesize array-type carbon nanotubes, and the resistivity of the product is too high, the specific surface area is too small, and it lacks practicality.
[0158] in addition, Figure 1 This is a sample photo of the hybrid material prepared in Application Example 2. Figure 2 is the SEM image of the hybrid material. Figure 2 It can be seen that the carbon nanotubes are aggregated and appear in a bundle shape as a whole, with an orderly growth direction rather than a random interweaving, indicating that array-type carbon nanotubes have been successfully synthesized.
[0159] Finally, it should be noted that the above application examples are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the above application examples, those of ordinary skill in the art should understand that they can still modify the technical solutions recorded in the above application examples, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the application examples of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in each application example can be combined in any way. The present application is not limited to the specific application examples disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A method for preparing a graphite-based metal catalyst precursor, characterized in that: The preparation method comprises: (1) Providing reaction solution A and reaction solution B The graphite oxide, the soluble metal salt and water are first mixed to obtain the reaction solution A; wherein the soluble metal salt includes a cobalt salt and an iron salt; The organic ligand, the alkali solution and the water are mixed for the second time to obtain the reaction solution B; (2) The reaction solution A and the reaction solution B are mixed for a third time to form a metal organic framework material including cobalt and iron on the surface of the graphite oxide.
2. The preparation method according to claim 1, characterized in that: The preparation method further comprises: The graphite is immersed in concentrated nitric acid, potassium permanganate and acetic acid are added to carry out an oxidation reaction to obtain the graphite oxide; Preferably, relative to 1g of the graphite, the amount of concentrated nitric acid used is 5-10mL, and the amount of acetic acid used is 2-5mL; the mass ratio of the graphite to potassium permanganate used is (1.5-3):1; Preferably, the oxidation reaction temperature is 20-40° C. and the time is 0.5-2 h.
3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of the iron salt to the cobalt salt is (1.2-7):1; Preferably, the iron salt is selected from at least one of ferric chloride, ferric nitrate, ferric sulfate and their respective hydrates; Preferably, the cobalt salt is selected from at least one of cobalt chloride, cobalt nitrate, cobalt sulfate and their respective hydrates; Preferably, the mass ratio of the graphite oxide to the soluble metal salt is (15-30):
100.
4. The preparation method according to any one of claims 1 to 3, characterized in that The organic ligand is at least one of 2-methylimidazole, terephthalic acid and phthalic acid, preferably 2-methylimidazole; Preferably, the mass ratio of the organic ligand to the soluble metal salt is (20-50):
100.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The alkali solution is selected from at least one of triethylamine, ammonia water and an aqueous solution of sodium hydroxide; Preferably, the amount of the alkali solution used is 0.2-0.8 mL, more preferably 0.3-0.5 mL, relative to 1 g of the organic ligand.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In step (2), the third mixing is carried out under stirring conditions, the stirring speed is 500 to 1200 rpm, the temperature of the third mixing is 50 to 80° C., and the time is 0.5 to 3 h; Preferably, the preparation method further comprises: The product obtained in step (2) is subjected to solid-liquid separation, washing, and drying to obtain a graphite-based metal catalyst precursor solid product; Preferably, the drying temperature is 90-150° C. and the drying time is 3-8 hours.
7. A graphite-based metal catalyst precursor prepared by the preparation method according to any one of claims 1 to 6.
8. A graphite-based metal catalyst, characterized in that The method is prepared by annealing the graphite-based metal catalyst precursor according to claim 7 under an inert atmosphere; Preferably, the annealing temperature is 650-750° C., and the annealing time is 20-70 minutes.
9. Use of the graphite-based metal catalyst precursor according to claim 7 or the graphite-based metal catalyst according to claim 8 in the preparation of array-type carbon nanotubes.
10. A method for preparing an array-type carbon nanotube / graphite hybrid material, characterized in that: include: In the presence of a catalytic material and under inert gas protection, a carbon source gas is used to perform chemical vapor deposition to form array-type carbon nanotubes, thereby preparing the array-type carbon nanotube / graphite hybrid material; wherein, The catalytic material comprises the graphite-based metal catalyst precursor of claim 7 or the graphite-based metal catalyst of claim 8; Preferably, the carbon source gas is selected from at least one of methane, ethane, propane, acetylene, ethylene and propylene; Preferably, the chemical vapor deposition conditions include: a carbon source gas flow rate of 1000 to 3000 sccm, a temperature of 650 to 750° C., and a time of 40 to 70 minutes; Preferably, the amount of the catalytic material used is 0.1-2 g relative to 1000 sccm of the carbon source gas.
11. The array carbon nanotube / graphite hybrid material prepared by the preparation method according to claim 10.
